Advanced anticorrosion coatings prepared from polybenzoxazine/siloxane‐containing epoxy resin. Issue 8 (26th May 2020) - Sili, He; Yuntao, Li; Chunxia, Zhao; Jiaojiao, Wu; Hui, Li; Dong, Xiang
Abstract: In this study, a new type of coating comprising benzoxazine and siloxane‐containing epoxy (SiEP) resin was prepared by the thermal curing method. The FTIR (Fourier transform infrared) analysis not only confirmed the complete reaction between polybenzoxaine and SiEP resin after heat curing, but also found the hydrogen‐bonding interactions between them. The addition of SiEP resin significantly enhanced the hydrophobicity and adhesion ability of the coating and greatly improved the water contact angles of the blend coatings (>108°), compared to that of the pristine PBa coating, which attributed to the introduction of a SiOSi network structure in the matrix. In addition, the corrosion resistance of the coating was tested though a series of electrochemical experiment. According to the results, the corrosion current values of the blend coatings decreased by about four orders of magnitude compared to that of the pristine carbon steel, and the corrosion protection efficiency of the blend coatings were >99%, indicating good application prospect of these blend coatings.